Edukasi Imunisasi Dasar Lengkap di Klinik Mitra Ananda Kota Palembang - Yulvira Febriani; Annisa Khoiriah; Maya Erisna (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2026)
Complete basic immunization is an effective preventive measure to reduce morbidity and mortality from vaccine-preventable diseases. However, many infants and toddlers still miss complete immunization, often due to a lack of knowledge and awareness among parents. This community service activity aims to enhance the knowledge and understanding of pregnant women, mothers with infants and toddlers, and caregivers about the importance of complete basic immunization. The activity was carried out at the Mitra Ananda Clinic in Palembang through education methods such as counseling, interactive discussions, and the distribution of educational media. A total of 33 participants, consisting of pregnant women and mothers with infants and toddlers, attended the session. Evaluation was conducted using pre-test and post-test questionnaires to assess changes in the participants' knowledge. The results showed a significant increase in participants' knowledge about the types, schedule, and benefits of complete basic immunization. Participants also demonstrated a positive attitude and commitment to ensuring that their children receive immunization according to the schedule. This activity is expected to contribute to the improvement of complete immunization coverage and help prevent diseases that can be avoided through vaccination